Teaching Proverbs Using Conceptual Metaphors: A Case Study of Kurdish EFL University Students - Kovan Rizgar Mustafa; Salam Neamah Hirmiz Hakeem (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The current study focuses on examining the effectiveness of the Conceptual Metaphor as part of cognitive linguistics in teaching and learning English idiomatic expressions among Kurdish EFL university students. The participants of this study are 62 sophomores in English Department, Soran University. They are enrolled in the course ‘Communication Skills’, first semester of the academic year 2022-2023. They are divided into the Control and Experimental groups, 31 students in each group. Students in both groups received instruction from the same lecturer for thirteen weeks. Instructional treatments were given to the Control group and Experimental group based on Traditional methods and Cognitive linguistics-approach (using conceptual metaphor), respectively. Pre- and Post-tests were used as the instruments of the study for data collection. The descriptive statistics of SPSS analysis, by Paired Samples t-tests, showed that students in Experimental group outperformed those in the Control group. With respect to the (p < 0.05), the difference between both groups was statistically significant in favor of the Experimental group (t = -6.229, .000). Besides, the difference between both groups associated with exposed proverbs is statistically significant in favor of the Experimental group (t = -2.882, p = .007). Additionally, the difference between both groups associated with unexposed proverbs is statistically different in favor of the Experimental group (t = -2.664, p = .012). The researchers recommend that the conceptual metaphor theory be used, as an alternative strategy in learning and teaching idiomatic expressions, specifically proverbs, in communication skills classes that involve speaking and listening.